Ultrasonic assisted hydrolysis of barley straw biowastes into construction of a novel hemicellulose-based adsorbent and its adsorption properties for Pb2+ ions from aqueous solutions. (December 2020) - Mohammadabadi, Siroos Iravani; Javanbakht, Vahid
Abstract: In this study, a chemical fractionation process using sulfuric acid was investigated to recover hemicellulose from barley straw under ultrasonic, and then, the extracted hemicellulose was mixed with sodium alginate to prepare the biosorbent with the gelation-solidification method. The prepared biosorbent was characterized by Field Emission Scanning Electron Microscope (FESEM), Energy-dispersive X-ray spectroscopy (EDX), Fourier transform infrared spectroscopy (FTIR), high-performance liquid chromatography (HPLC), and Brunauer-Emmett-Teller (BET) surface area analysis and used for efficient toxic lead removal from aqueous solutions. Different factors influencing adsorption, mechanisms, kinetics, isotherms, and thermodynamics were explored. The rate-controlling step in the early stages of adsorption was film diffusion that was determined by Boyd, Webber, and Dubinin-Radushkevich models. The maximum Pb 2+ adsorption capacity was obtained 277.78 mg/g in pH = 5, 0.4 g/L adsorbent dosage, 210 mg/L initial Pb 2+ concentration, and 55 °C temperature and the removal efficiency was over 99%. Besides, after 5 reuse cycles, the high lead adsorptivity was observed. Due to the benefits of the prepared biosorbent such as high adsorption capacity, renewability, low-cost, and biodegradability, they can be effective adsorbents for the treatment of heavy metals wastewaters. Graphical abstract: Image 1 Highlights: Barley straw was hydrolyzed to extract hemicellulose under ultrasonic. Cross-linked biocomposite of extracted hemicellulose was successfully prepared. The biocomposite was used for enhanced lead removal from aqueous solution.